2012
DOI: 10.1007/s13369-012-0333-z
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strengthening of Short Span Reinforced Concrete Beams with CFRP Sheets

Abstract: This paper presents the results of a series of tests on short span reinforced concrete beams which were strengthened in shear with various arrangements of externally bonded Carbon Fibre Reinforced Polymer (CFRP) sheets. The objective of the tests was to determine the effect of changing the area and location of the CFRP sheet within the shear span. A total of fifteen 150 mm x 300 mm x 1,675 mm concrete beams were tested of which four were un-strengthened control specimens. The remaining eleven beams were streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 15 publications
0
2
0
7
Order By: Relevance
“…(3). The proposed STM also provided reasonable predictions of the shear strength of members strengthened over the full depth of the beam using externally bonded CFRP sheets [10,37]. STMs generally neglect size effect.…”
Section: Existing Design Formulas and Proposed Strut-and-tie Modelmentioning
confidence: 63%
“…(3). The proposed STM also provided reasonable predictions of the shear strength of members strengthened over the full depth of the beam using externally bonded CFRP sheets [10,37]. STMs generally neglect size effect.…”
Section: Existing Design Formulas and Proposed Strut-and-tie Modelmentioning
confidence: 63%
“…Phần lớn nghiên cứu trước đây được tiến hành trên các mẫu dầm gia cường chịu uốn, có kích thước nhỏ và trong phạm vi phòng thí nghiệm [6][7][8]. So với gia cường chịu uốn, các nghiên cứu về gia cường chịu cắt cho dầm BTCT thì có số lượng ít hơn và chủ yếu được tiến hành trên các mẫu dầm có tiết diện chữ nhật hoặc chữ T, với kích thước hạn chế [9][10][11][12][13][14][15]. Cho đến nay, nghiên cứu về khả năng chịu cắt của dầm gia cường bằng CFRP vẫn là một chủ đề được các nhà khoa học quan tâm, đặc biệt đối với dầm bê tông không cốt thép đai [16][17][18][19][20].…”
Section: Giới Thiệuunclassified
“…Các tham số về vật liệu và các kết quả đặc trưng cho ứng xử cơ học của dầm như biểu đồ tải trọng -chuyển vị, sơ đồ vết nứt và dạng phá hoại được thu thập từ một nghiên cứu thực nghiệm của Bukhari và cs. [14]. Việc so sánh giữa kết quả mô hình và kết quả thực nghiệm cho phép khẳng định rằng các mô hình PTHH có khả năng dự báo chính xác khả năng chịu cắt của dầm đối chứng và các dầm gia cường, cũng như cho phép mô phỏng sơ đồ vết nứt bê tông và các dạng phá hoại xảy ra (phá hoại cắt, bong tách tấm CFRP, hư hỏng tấm CFRP).…”
Section: Giới Thiệuunclassified
See 1 more Smart Citation
“…Carbon fiber-reinforced polymer (CFRP) is used to strengthen reinforced concrete structural members in shear and flexure because of their superior mechanical properties in terms of high strength-to-weight ratio, corrosion resistance, thermal resistance and ease of use (Hollaway et al , 2008). Several experimental research on CFRP has shown the effectiveness of using externally bonded CFRP composites to improve the flexural and shear strength of RC structural members (Jiangfeng et al , 2013; Bukhari et al , 2013). CFRP composites improve the performance and ductility of the structural behavior of RC beams (Al-Hadithy and Al-Ani, 2016).…”
Section: Introductionmentioning
confidence: 99%